2023
DOI: 10.1371/journal.pone.0281528
|View full text |Cite
|
Sign up to set email alerts
|

HIV virologic response, patterns of drug resistance mutations and correlates among adolescents and young adults: A cross-sectional study in Tanzania

Abstract: Background The emergence of HIV drug resistance mutations (DRMs) is of significant threat to achieving viral suppression (VS) in the quest to achieve global elimination targets. We hereby report virologic outcomes and patterns of acquired DRMs and its associated factors among adolescents and young adults (AYA) from a broader HIV drug resistance surveillance conducted in Tanzania. Methods Data of AYA was extracted from a cross-sectional study conducted in 36 selected facilities using a two-stage cluster sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This finding is consistent with studies conducted in the Ehlanzeni district of South Africa (74%), Uganda (75.8%), Kumasi, Ghana (76.1%), and the East Shewa zone of Oromia, Ethiopia (72%)(13–16). However, this finding is lower than those of studies conducted in the USA (86%)(17), Buenos Aires, Argentina (87.3%)(18), Cameroon (88.2% and 94.55%)(19, 20), Uganda (81%, 85%, & 85.7%)(2123), Bamako, Mali (100%)(24), Mazowe, Zimbabwe (94.4%)(25), Tanzania (91.5%)(26), South Africa (77% and 77.2%)(27, 28), Kenya (80% and 90%) (29, 30), Ethiopia (82% and 82.39%) (10, 31). The ambitious 95-95-95 approach put forth by USAID, WHO, and UNAIDS to achieve 95% viral load suppression by 2030 is too far from the current results (5, 32).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with studies conducted in the Ehlanzeni district of South Africa (74%), Uganda (75.8%), Kumasi, Ghana (76.1%), and the East Shewa zone of Oromia, Ethiopia (72%)(13–16). However, this finding is lower than those of studies conducted in the USA (86%)(17), Buenos Aires, Argentina (87.3%)(18), Cameroon (88.2% and 94.55%)(19, 20), Uganda (81%, 85%, & 85.7%)(2123), Bamako, Mali (100%)(24), Mazowe, Zimbabwe (94.4%)(25), Tanzania (91.5%)(26), South Africa (77% and 77.2%)(27, 28), Kenya (80% and 90%) (29, 30), Ethiopia (82% and 82.39%) (10, 31). The ambitious 95-95-95 approach put forth by USAID, WHO, and UNAIDS to achieve 95% viral load suppression by 2030 is too far from the current results (5, 32).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found no associations between PLLV and age or sex, which is consistent with previous research that reported no links between client demographics and PLLV. 11 , 13 , 72 74 The absence of correlation between PLLV and individuals’ most recent World Health Organization clinical stage suggests that dolutegravir-based ART is effective in achieving and maintaining viral suppression in most clients, regardless of their demographic or clinical characteristics. 75 , 76 Also, the consistency of PLLV outcomes irrespective of the Differentiated Service Delivery model lends credibility to reports that Differentiated Service Delivery does not compromise the virological efficacy of dolutegravir-based ART.…”
Section: Discussionmentioning
confidence: 99%
“… 20 It is noteworthy that Case 2 re-engaged with each pregnancy, a common pattern of re-engagement among female patients. 21 Unfortunately, with increasing reports of DTG resistance, 9 , 10 clinicians in South Africa need to be aware that, although DTG is robust, resistance remains a possibility in a small proportion of individuals. This case series adds to the evidence raising concerns that in programmatic settings, DTG resistance may be more frequent than predicted, particularly in contexts where inadequate adherence support and VL monitoring result in prolonged periods of viral non-suppression.…”
Section: Discussionmentioning
confidence: 99%
“…However, within programmatic settings, reports of DTG resistance are emerging, including a 5.8% rate of DTG-resistant mutations among adolescents and young adults in a Tanzanian national survey. 9 A recent article also described South Africa’s first published case of DTG resistance, in a treatment-experienced, integrase strand inhibitor (InSTI)-naïve adolescent. 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation